Memperkasakan Budaya Berfikir Islam: Suatu Analisis - Abd. Rahim, Rahimin Affandi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2002)
Basically this article focusses upon the concept of Islamic thinking that has been elucidated by many Muslim scholars. The discussion is divided into several sections, namely the historical analysis of the degeneration and renewal of Muslim intelectual tradition pertaining to the nature of Islamic thinking, the Muslim concept of thinking and its connection with the reformation movement and finally the obstacle toward the prolongation of Islamic thinking in the modern world.